Immunomodulatory effect of vitamin D on the STATs and transcription factors of CD4+ T cell subsets in pregnant women with preeclampsia - Ribeiro, Vanessa Rocha [UNESP]; Romao-Veiga, Mariana [UNESP]; Nunes, Priscila Rezeck [UNESP]; de Oliveira, Larissa Ragozo Cardoso [UNESP]; Romagnoli, Graziela Goretti; Peracoli, Jose Carlos [UNESP]; Peracoli, Maria Terezinha Serrao [UNESP] (Elsevier, 2022)
This study evaluated the in vitro modulatory effect of vitamin D (VD) on T cells, by determining the expression of STATs and the transcription factors of each CD4+ T cell subsets. Twenty women with preeclampsia (PE) and 20 normotensive pregnant women were studied. Peripheral blood mononuclear cells were cultured with or without VD to analyse the STATs and transcription factors by flow cytometry, and cytokines production by ELISA. The plasma levels of VD were lower in the PE group. Treatment of cells with VD decreased STAT1/STAT4/T-bet, STAT3/RORγt, and increased STAT6/GATA-3 and STAT5/FoxP3 in preeclamptic women. Treatment with VD also decreased the levels of inflammatory cytokines and increased IL-10 and TGF-β. This hormone exerts immunomodulatory effects on the STAT signalling pathway, shifting the inflammatory profiles, Th1/Th17 cells to Th2/Treg profiles, and it can be suggested as a promising strategy to regulate the systemic inflammatory response in PE.
Keywords: Activators of transcription; Preeclampsia; T cell subsets; Transcription factors; Vitamin D